1969
DOI: 10.1007/bf02279132
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of growth and resorption of bone in rats fed meat diet

Abstract: Different coloured, fluorescent bone-s~eking chemicals, viz., tetracycline, Alizarin Red S, and DCAF, have been administered sequentially to weanling rats and the rate of formation and resorption of bone measured from hard-ground cross sections of the upper third of the diaphysis of the fenmr. On a meat diet, bodily growth is significantly restricted for the first week and then recovery occurs. While bones grow they fail to mineralize normMly and rapidly become fragile and rarefied. Resorption of bone is at fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1972
1972
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Our cointrol value for the periosteal mineralization rate, 3.57+0.43 gnm/day, correlates with the value of 3.2 ,tm/dav reported by previous investigators as the periosteal f'ormation rate in the femur of rats of similar weight (22). Subsequent studies by others with the rat tibia have reported periosteal and endosteal formation rates of 6.0 ,um/day and 2.9…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our cointrol value for the periosteal mineralization rate, 3.57+0.43 gnm/day, correlates with the value of 3.2 ,tm/dav reported by previous investigators as the periosteal f'ormation rate in the femur of rats of similar weight (22). Subsequent studies by others with the rat tibia have reported periosteal and endosteal formation rates of 6.0 ,um/day and 2.9…”
Section: Discussionsupporting
confidence: 89%
“…The discrepancies in the reported bone mineralization rates in rats (22)(23)(24)(25) are most likely a result of differences in the experimental conditions, the weights and ages of the animals, and the bones studied. Both the rat tibia and f'emur are complicated by structural asymmetry and cortical drift (25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Suprisingly, only a very small number of studies have focused attention with respect to bone health on populations consuming a diet highly dependent on animal foods, particularly that of meat (Hammond & Storey 1970). Mazess & Mather (1974) examined the bone mineral content of forearm bones in a population sample of Eskimo natives living off the north coast of Alaska.…”
Section: Vegetarianism and Its Implications For Bone Healthmentioning
confidence: 99%
“…While some studies published prior to 1990 found bone mineral mass to be higher in vegetarians, the five most recent studies carried out in the last decade have suggested no differences in bone mass between vegetarians and omnivores. Suprisingly, only a very small number of studies have focused attention with respect to bone health on populations consuming a diet highly dependent on animal foods, particularly that of meat (Hammond & Storey 1970). Mazess & Mather (1974) examined the bone mineral content of forearm bones in a population sample of Eskimo natives living off the north coast of Alaska.…”
Section: Vegetarianism and Its Implications For Bone Healthmentioning
confidence: 99%
“…1954[Kropp. , 1956Friend and Smith, 1964;Strndström, 1966;Hammond andStorey, 1972: Mc Queen et al. 1972;Holmstrand, 1975: Malcolm, 1975: Eger.…”
Section: Anforderung An Knochenschlitfementioning
confidence: 99%